К вопросам таксономии, репродукции и распространения Nitzschia longissima (Bréb.) Grunow (Bacillariophyta) - Шоренко, К.И.; Давидович, О.И.; Давидович, Н.А. (Альгология, 2013)
Рассмотрены вопросы таксономии, репродукции и распространения диатомовой водоросли Nitzschia longissima. На основании анализа литературных данных, а также изучения типового материала вида и 36 клонов, отобранных на атлантическом побережье Франции и в Черном море (район Карадага), предложено применять в отношении N. longissima концепцию sensu stricto, которая, по мнению авторов, устранит многие накопившиеся проблемы в идентификации вида. Розглядаються питання таксономії, репродукції і розповсюдження діатомової Nitzschia longissima. На підставі аналізу літературних даних, а також вивчення типового матеріалу виду і 36 клонів, відібраних з атлантичного узбережжя Франції і в Чорному морі в районі Карадага, ми пропонуємо застосовувати відносно N. longissima концепцію sensu stricto, яка, з нашої точки зору, усуне багато накопичених проблем в ідентифікації виду. By now, sufficient factual material relating to the diatom alga Nitzschia longissima has been accumulated in the literature. At the same time, there is a mistaken understanding of the features of N. longissima in some studies, apparently because the authors of these publications ignored data on internal structures of cells and misunderstood or disregarded data on the life cycles and reproduction of the species. Obviously, all floristic data obtained with the use of information based on a broad understanding of the species will also be questionable. Under the name N. longissima several species are hidden. They belong to a heterogeneous complex longissima—closterium—reversa. Based on the analysis of literature data, as well as on the study of type material and thirty-six clones, gathered on the Atlantic coast of France and in the Black Sea near Karadag, we proposed to apply to N. longissima a concept sensu stricto, which may eliminate many problems in the identification of this species.